If It's Constitutional, Then What's the Problem?: The Use of Judicial Override in Alabama Death Sentencing - Shannon Heery (Washington University Journal of Law & Policy, 2010)
This Note focuses on the history of Alabama‘s death sentencing law as a window into the rationale requiring abrupt change. Part I.A addresses the Supreme Court‘s death penalty jurisprudence following Furman v. Georgia. Part I.B follows with Supreme Court opinions regarding judicial override. Part I.C considers Apprendi v. New Jersey and Ring v. Arizona to demonstrate the increased role of the jury in capital sentencing. Part I.D explores Alabama‘s current state of judicial override through an examination of (1) its statutory scheme, (2) Alabama cases following Ring, (3) Alabama death penalty statistics, and (4) recent public outcry criticizing the system and the responses of state officials. Part II of this note analyzes the Alabama law and proposes changes.
Keywords: Capital punishment -- United States; Sentences (Criminal procedure) -- United States; Jury decision making; Judicial discretion; Aggravating circumstances (Law); Furman v. Georgia 408 U.S. 238 (1972); Cruel and unusual punishment; Judicial power; Alabama